Teachers' Growth Mindset and Work Engagement in the Chinese Educational Context: Well-Being and Perseverance of Effort as Mediators - Zeng, Guang; Chen, Xinjie; Cheung, Hoi Yan; Peng, Kaiping (Frontiers in Psychology, 2019)
The current study investigated the relationships among growth mindset, work engagement, perseverance of effort and well-being for secondary school teachers in the Chinese educational context. We adopted Growth Mindset Inventory, Utrecht Work Engagement Scale (UWES), Grit Scale (Perseverance subscale), and PERMA profiles that measure five dimensions of well-being. Participants included 472 secondary school teachers from 10 secondary schools in central China. Correlation analysis showed that growth mindset, well-being, and perseverance of effort could all predict work engagement. Moreover, the structural equation model and mediation analysis further suggested that well-being and perseverance of effort could partially mediate the relationship between growth mindset and work engagement. This study permitted to advance our knowledge about the relationship between growth mindset and work engagement, which should be considered for future teaching practices and teacher development.